A Program Based on Common Technology to Support Communication Exchanges and Leisure in People With Intellectual and Other Disabilities. Issue 6 (November 2019) - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Alberti, Gloria; Chiariello, Valeria; Campanella, Caterina; Grillo, Giovanna; Tagliente, Vincenzo
The aim of this study was to assess a new smartphone-based program version to allow seven participants with intellectual plus visual and/or motor disabilities and hesitant speech to send out and receive WhatsApp messages, make telephone calls, and access leisure activities. This program version relied on a Samsung A3 smartphone, which was automated through the MacroDroid application and responded to the input of specific cards and miniature objects. During the baseline (i.e., without the program), the participants' performance was zero or close to zero on communication and leisure. During the use of the program, the participants increased their frequency of WhatsApp messages sent out and received/listened to, and of leisure activities accessed. Their frequency of telephone calls averaged between virtually zero and slightly above one. The implications of the findings are discussed in relation to the technology used for the program and the applicability of the program in daily contexts.